P660 A pilot elastography study in patients with inflammatory bowel disease on long-term treatment with azathioprine. (16th January 2018) - Mantzaris, G J; Hatzievagelinou, C; Karampekos, G; Filippidis, G; Gkeros, F; Tziortziotis, I; Vraka, M; Christidou, A; Mela, M; Viazis, N
Abstract: Background: Azathioprine (AZA) is generally effective in maintaining remission in patients with steroid-dependent Crohn's disease (CD) and ulcerative colitis (UC). However, long-term treatment is associated with an increased risk of haematological and skin malignancies and may be a risk factor nodular regenerative hyperplasia (NRH) in male CD patients with extensive ileal resections and for hepatic fibrosis. In this prospective, single-centre, pilot study we aimed to assess the risk for hepatic fibrosis in IBD patients on long-term AZA treatment using hepatic elastography. Methods: Between April 1 and October 30, 2017 consecutive patients with CD or UC, aged 18–65 years, in remission on AZA for ≥3 years who consented to participate were included in this study. Exclusion criteria were pre-existing liver disease, abnormal liver function tests (LFTs), alcohol impingement, cholelithiasis, diabetes mellitus, lipid disorders, and prior cholecystectomy. Patient demographic, social habits and clinical data were recorded, the Body Mass Index (BMI) was calculated, and an upper abdominal ultrasound was performed before elastography to assess for any insidious liver disease. Liver elastographies were performed by two independent well-trained physicians using a single, calibrated equipment and the hepatic stiffness (KPa) was calculated as the median (IQR) of 10 measurements. Values above 7.0 kPa were considered abnormal. Patients with abnormal or borderline hepatic stiffness had a repeat test 1 year later. Results: Thirty-three patients were included [20 females, median age (range) 38.5 (−64) years, 25 with CD, 15 smokers]. The median time (range) of AZA treatment was 6.8 (3.5–17) years. The median BMI was 21.94 (17.1–30). Five CD patients had ultrasonographic evidence of fatty liver disease but normal LFTs. Sixteen CD patients had undergone right hemicolectomy before ( n = 13) or after ( n = 3) initiation of AZA. The median kPa was 4.5 (rate 2.1–8.5). Sixteen patients had a repeat elastography after one and four patients after 2 years without significant differences in hepatic stiffness from baseline. During the follow-up none of the patients developed abnormal LFTs. However, three CD patients with fatty liver disease and a BMI ≥27 had abnormal kPa values within a 1-year period [7.6 of 7.8, 7.5 of 7.6 and 8.0 of 8.5, respectively). Conclusions: This pilot study shows that patients with IBD in remission on long-term AZA treatment have normal values of hepatic stiffness. However, patients with fatty liver disease irrespective of normal LFTs may be in increased risk and should be followed closely. Studies of a larger patient cohort are essential to assess the actual risk of hepatic fibrosis in these patients.